Love and belonging across cultures: a comparative study of two Asian short stories - Thoyib, Muhammad Edy; Humairoh, Jihan Al (UNIB Press, 2025)
Love and belonging are universal and essential to human needs as they transcend cultural boundaries. This comparative study conducts an analysis of Xi Xi's A Woman Like Me, set in Hongkong, and Agus Noor's Kisah Cinta Perempuan Perias Mayat, set in Indonesia. Both short stories narrate the struggles of their protagonists with love, belonging, rejection, and social isolation. Therefore, this study aims to analyze how the social stigma associated with professional activities related to or leading to death stands in the protagonists' way in regard to satisfying their emotional needs, to establish how social rejection and isolation contribute to their self-concept development, and to show attempts they make to fulfill the need to be loved and to belong in spite of cultural barriers. This literary criticism applies Maslow's Hierarchy of Needs and a qualitative comparative literature approach to illustrate the cross-cultural challenges in Hong Kong and Indonesia. The results indicate that while both protagonists strive for love and belonging, they are alienated by society due to their professions. Cultural aspects also revealed how Hong Kong and Indonesia's view of death shape their experiences of rejection. This study places emphasis on the intersection of character motivation in the pursuit of love and belonging, societal isolation and rejection caused by negative stigmatisation across cultures.